Networks and Subjectivity in Contemporary French Philosophy - DOI: 10.3395/reciis.v1i1.35en - André Parente (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2007)
This article presents three different perspectives on networks in contemporary French philosophy, in particular the thinking of Paul Virilio, Michel Foucault and Bruno Latour. What we call transformative networks, in line with Bruno Latour, are socio-technical mediations which are altering the conditions of the experience and producing new forms of subjectivity. Networks are empirical figures of the ontology of the present, figures which permit us to think about the field of communication as a contemporary structural problem.